Time remaining:
show work for 11. ANSWER ALL :)

label Algebra
account_circle Unassigned
schedule 0 Hours
account_balance_wallet $5

Feb 16th, 2015

11.
subtracting 2nd equation from the 1st equation.

6x+3y =-12
6x + 2y =-4
-     -       +
____________
y = 8

putting the value of  y=16 in 1st equation.
6x +3*8 =-12
6x =-12-24
6x = -36
x =-6

so, x =-6 and y=8


12.
y=2x+11
y+x =5

rewriting them,
y-2x=11
y+x=5

subtracting 2nd equation from the 1st equation.
y - 2x = 11
y + x = 5
-  -      -
_________
-3x = 6
x =-2

and putting the value of x = -2 in 1st equation...

y =2*-2 +11 = -4+11 =7

so, x=-2 and y=7


13. (-1,0)


14. (-1,7)

Feb 16th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Feb 16th, 2015
...
Feb 16th, 2015
Sep 25th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer